2009
DOI: 10.1093/rheumatology/kep375
|View full text |Cite
|
Sign up to set email alerts
|

The RIG-I-like receptor IFIH1/MDA5 is a dermatomyositis-specific autoantigen identified by the anti-CADM-140 antibody

Abstract: The anti-CADM-140 antibody was a marker of DM and intractable ILD and recognized IFIH1/MDA5, which is involved in innate immunity. These findings may give a new insight into the pathogenesis of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
294
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(306 citation statements)
references
References 31 publications
9
294
2
1
Order By: Relevance
“…7,8 The development and rapid progression of ILD may account for the significantly higher mortality observed in anti-MDA5-positive-DM patients as compared to serologically negative cohorts. 6,14,18,19 Generally, skin manifestations precede ILD in these patients. 14 Previous studies have shown a correlation between ferritin levels and ILD activity, as well as an association between elevated ferritin levels and mortality in patients with anti-MDA5-positive-DM.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The development and rapid progression of ILD may account for the significantly higher mortality observed in anti-MDA5-positive-DM patients as compared to serologically negative cohorts. 6,14,18,19 Generally, skin manifestations precede ILD in these patients. 14 Previous studies have shown a correlation between ferritin levels and ILD activity, as well as an association between elevated ferritin levels and mortality in patients with anti-MDA5-positive-DM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anti-CADM140 antibody was also named anti-MDA-5 antibody and was known to be associated with CADM and ILD in recent publications (11)(12)(13)(14). To establish the clinical relevance of anti-MDA-5 antibodies, we examined the antibody in the sera of Chinese patients with various connective tissue diseases (CTDs), and further delineated the clinical course of patients with a positive expression of anti-MDA-5 antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…RIG-I and IFIH1 interact with viral RNA and mediate signalling pathways leading to the transcription of type I interferons (IFNs) and inflammatory cytokines (Takeuchi & Akira, 2008). The finding that IFIH1 provokes MSA reinforces the idea of an association between myositis and viral infection: self-tolerance might be broken when IFIH1 interacts with certain viral RNAs and generates cryptic epitopes or when elevated IFN-levels up-regulate IFIH1 synthesis, resulting in over-expression and release from damaged cells (Nakashima, 2010). It is not well understood how a self-molecule can be singled out as target for autoantibody response.…”
Section: Autoantibodiesmentioning
confidence: 87%
“…Anti-small ubiquitin-like modifier activating enzyme (SAE) antibodies are found in about 8% of DM patients (Ghirardello et al, 2010). A novel MSA -anti-CADM-140 antibody -was identified recently in a Japanese cohort of DM patients (Nakashima et al, 2010). These antibodies seem particularly associated with clinically amyopathic DM who also have acute progressive interstitial lung disease.…”
Section: Autoantibodiesmentioning
confidence: 99%